Bacterial cellulose tubes as a nerve conduit for repairing complete facial nerve transection in a rat model - BİNNETOĞLU, ADEM; BATMAN, ABDULLAH ÇAĞLAR; AKAKIN, DİLEK (SPRINGER, 2020)
Purpose Functionality of the facial nerve is cosmetically important. While many techniques have been investigated, early and effective treatment for traumatic facial nerve paralysis remains challenging. Here, we aim to examine bacterial cellulose (BC) as a new tubularization material for improving facial nerve regeneration. Methods Our study was performed on 40 female Sprague Dawley rats. Rats were randomly divided into four groups, with 10 rats per group. In all rats, the main trunk of the facial nerve was completely cut 8 mm before the branching point. For repairing the facial nerve, in group 1, the nerve was left to recover spontaneously (control group); in group 2, it was repaired by primary suturing (8.0 Ethilon sutures, Ethicon); in group 3, BC tubes alone were used to aid nerve repair; and in group 4, both BC tubes and primary sutures (8.0 Ethilon sutures) were used. After 10 weeks, the facial nerve regeneration was evaluated by the whisker movement test and electrophysiologically (nerve stimulation threshold and compound muscle action potential). Nerve regeneration was assessed by calculating the number of myelinated nerve fibers, and by microscopically evaluating the amount of regeneration and fibrosis. Results No significant difference was observed among the groups in terms of whisker movement and electrophysiological parameters (P > 0.05). We found that the numbers of regenerating myelinated fibers were significantly increased (P < 0.05) when BC tubes were used as a nerve conduit. Conclusions BC can be easily shaped into a hollow tube that guides nerve axons, resulting in better nerve regeneration after transection.
Keywords: Facial nerve; Peripheral nerve trauma; Neurotmesis; Bacterial cellulose; Tubularization; REGENERATION; MANAGEMENT; SURGERY; TISSUE; GRAFT